Role of hepatic stellate cells in liver ischemia-reperfusion injury - Peng, Yuming; Yin, Qiang; Yuan, Miaoxian; Chen, Lijian; Shen, Xinyi; Xie, Weixin; Liu, Jinqiao (Frontiers in Immunology, 2022)
Liver ischemia-reperfusion injury (IRI) is a major complication of liver trauma, resection, and transplantation. IRI may lead to liver dysfunction and failure, but effective approach to address it is still lacking. To better understand the cellular and molecular mechanisms of liver IRI, functional roles of numerous cell types, including hepatocytes, Kupffer cells, neutrophils, and sinusoidal endothelial cells, have been intensively studied. In contrast, hepatic stellate cells (HSCs), which are well recognized by their essential functions in facilitating liver protection and repair, have gained less attention in their role in IRI. In addition, we discuss the regulation of liver repair and regeneration after IRI by HSCs. Finally, we provides a comprehensive summary of the effects of HSCs on the injury stage of liver IRI and their associated molecular mechanisms.